2008
DOI: 10.1152/ajpcell.00223.2008
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensing machinery for cells under low substratum rigidity

Abstract: Wei WC, Lin HH, Shen MR, Tang MJ. Mechanosensing machinery for cells under low substratum rigidity. Am J Physiol Cell Physiol 295: C1579 -C1589, 2008. First published October 15, 2008 doi:10.1152/ajpcell.00223.2008.-Mechanical stimuli are essential during development and tumorigenesis. However, how cells sense their physical environment under low rigidity is still unknown. Here we show that low rigidity of collagen gel downregulates ␤ 1 -integrin activation, clustering, and focal adhesion kinase (FAK) Y397 ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
71
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 62 publications
11
71
0
Order By: Relevance
“…Because only the rigidity changes between the different polyelectrolyte multilayers used in this study, the film stiffness is probably at the origin of the cell adhesion processes. This hypothesis agrees with a recent study, demonstrating that MDCK cells can sense the substratum rigidity to a sufficient extent to induce 1-integrin activation and clustering, allowing actin organization and downstream activation events to occur (Wei et al, 2008). In our present study, low rigidity above 50 kPa is sufficient for v-integrin engagement, allowing little cell spreading.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Because only the rigidity changes between the different polyelectrolyte multilayers used in this study, the film stiffness is probably at the origin of the cell adhesion processes. This hypothesis agrees with a recent study, demonstrating that MDCK cells can sense the substratum rigidity to a sufficient extent to induce 1-integrin activation and clustering, allowing actin organization and downstream activation events to occur (Wei et al, 2008). In our present study, low rigidity above 50 kPa is sufficient for v-integrin engagement, allowing little cell spreading.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, we could not exclude flow and creep phenomena of the film, and also a lateral cell pulling over several microns. It was previously reported that tyrosine phosphorylation increased at the adhesion sites of cells on stiff surfaces (Pelham and Wang, 1997;Giannone and Sheetz, 2006) and that the level of FAK-Y397 phosphorylation was progressively dependent on substratum rigidity (particularly at 390 Pa) on polyacrylamide gel for MDCK (Wei et al, 2008). In the present system, FAK-Y397 was only phosphorylated at around 200 kPa (E200) and again activated on the hard substratum (0/2, 0/5 and 0/12 and glass surfaces).…”
Section: Discussionmentioning
confidence: 47%
“…40 The cell lysates were harvested, resolved on SDS-PAGE, and then electrophoretically blotted onto nitrocellular paper. The primary antibodies used in this study are listed as follows: Klf4, cyclin D1, glyceraldehyde-3-phosphate dehydrogenase (Santa Cruz Biotechnology), Klf5 (Millipore, Temecula, CA), a-smooth muscle actin (Sigma-Aldrich), b1 integrin (BD Biosciences PharMingen), p-ERK, and ERK (Cell Signaling).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…28,29 The monoclonal antibodies against ␤ 1 integrin, E-cadherin, and fibronectin were purchased from BD Biosciences (San Jose, CA). Antibodies against integrins ␣ 1 , ␣ 2 , ␣5, and ␣ v were all purchased from Millipore (Billerica, MA).…”
Section: Western Blottingmentioning
confidence: 99%